Resenha de: Documenta Malucensia - Besselaar, José Van Den (Revista de História, 1975)
JACOB S. J. (Hubert), (Editor). — Documenta Malucensia —Vol . I(1524-1577).  Rome, "Institutum Historicum Societatis Jesu", in: MonumentaHistorica Societatis Jesu,  Vol. 109 — XLII + 84* + 758páginas.